GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 2981 species occurrences available in GBIF matching the query: TaxonKey: Spodoptera exigua Hübner, 1803/08. The dataset includes 2981 records from 70 constituent datasets: 4 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1 records from Catálogo de insectos de la colección del Centro de Entomología. 7 records from Collection entomologique Barthélémy. 16 records from Staffordshire Ecological Record - SER Species-based Surveys. 6 records from iNaturalist research-grade observations. 1 records from Merseyside BioBank - North Merseyside Insects (unverified). 32 records from Essig Museum of Entomology. 181 records from Tiroler Landesmuseum Ferdinandeum. 29 records from Biological and palaeontological collection and observation data MNHNL. 1 records from TESRI-FB-EnjoyMoths. 372 records from Insect (KNAM-IN). 217 records from Biological Records Centre - Moths - John Heath Lepidoptera recording scheme macro-moth data from BRC. 20 records from European Moth Nights. 1 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 19 records from Museum Victoria provider for OZCAM. 149 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 46 records from Biodiversitätsdatenbank des Landes Salzburg. 1 records from Insect specimen database of Atugi City Museum. 2 records from Insect (JJHA-IN). 7 records from Natural History Museum (London) Collection Specimens. 5 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2 records from RBINS collections. 172 records from Landesmuseum Kärnten. 1 records from BioBlitz Barcelona 2010-14. 1 records from Insect Specimen Database of Fukui City Museum of Natural History. 191 records from Moths Ireland. 10 records from Geographically tagged INSDC sequences. 1 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 2 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Université Pédagogique Nationale de Kinshasa- Les Insectes Comestibles de la R.D. Congo (Entomophagie). Projet CABIN (Central African Biodiversity Information Network). 2 records from Kashihara City Museum of Insect. 16 records from New Mexico Biodiversity Collections Consortium database. 2 records from National Museum of Natural Science. 17 records from Natural History Museum Rotterdam (NL) - Insecta collection. 160 records from Finnish Entomological Database: Lepidoptera. 2 records from Natural History Museum Rotterdam (NL) - Lepidoptera observations. 1 records from Genebank, National Institute of Agrobiological Sciences. 1 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 12 records from Lund Museum of Zoology - Insect collections (MZLU). 288 records from Bugbase, Lepidopterological Society. 67 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 5 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 16 records from Insect Collection of Taiwan Forestry Research Institute. 102 records from Australian National Insect Collection. 20 records from University of Alberta Entomology Collection (UASM). 1 records from naturgucker. 12 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 16 records from Taiwan Forestry Research Institute. 421 records from Biologiezentrum Linz. 10 records from Artdata. 103 records from Data on moths from automatically operating light traps in Denmark. 22 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Lepidoptera Observation Records. Pre-2010 for Cumbria. 19 records from Sussex Biodiversity Record Centre - Sussex Moth data for 2011 and 2012 DEFRA FUNDED. 3 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 6 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Lepidóptera. 6 records from Australian Museum provider for OZCAM. 59 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 2 records from Naturhistorisches Museum Mainz, Zoological Collection. 45 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 7 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 6 records from Akita Prefectural Museum, Insect Collection. 2 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 1 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 1 records from Natural History Museum Maastricht (NL) - Entomological Collection. 10 records from inatura - Erlebnis Naturschau Dornbirn. 5 records from Norwegian Lepidoptera working group. 4 records from Especímenes INBio. 5 records from Insect (MNHM-IN). 5 records from Lepidoptera collection of Hannu Saarenmaa.
Keywords: GBIF; biodiversity; species occurrences